EVALUATION OF NURSES' PERFORMANCE IN PRIMARY PREVENTION OF DIABETES MELLITUS - Umarova Shodiyabonu Abdurakhmon kizi (Web of Journals Publishing, 2025)
Type 2 diabetes mellitus is one of the most pressing public health problems of the 21st century, the prevalence of which continues to grow rapidly. In conditions of high morbidity, primary prevention aimed at preventing the development of the disease in individuals from risk groups is of particular importance. This article examines the role of a nurse in the primary prevention of diabetes mellitus. The areas of activity, functions, difficulties and prospects are analyzed, and practical recommendations for improving nursing preventive work in outpatient services are given. Particular attention is paid to the educational, screening and motivational functions of the nurse, as well as the effectiveness of her interaction with patients.
Keywords: type 2 diabetes mellitus, primary prevention, nurse, risk factors, nursing care, behavioral correction, screening, risk groups.